2021
DOI: 10.1177/23743735211007834
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction With Chronic Pain Management: Patient Perspectives of Improvement

Abstract: Integrating satisfaction measures with pain-related variables can highlight global change and improvement from the patients’ perspective. This study examined patient satisfaction in an interdisciplinary chronic pain management program. Nine hundred and twenty-seven (n = 927) participants completed pre- and post-treatment measures of pain, depression, catastrophizing, anxiety, stages of change, and pain acceptance. Multiple regression was used to examine these variables at admission and discharge as predictors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…30,31 Improvement in these affective and functional domains has been associated with greater levels of satisfaction with treatment. 32 This evidence further highlights the importance of pain management which focuses beyond merely the reduction of pain severity to equipping chronic pain patients with the tools to help them participate in meaningful life roles and to reduce pain interfering with function. The one area that participants were less satisfied with in their pain management related to the amount of information received.…”
Section: Discussionmentioning
confidence: 95%
“…30,31 Improvement in these affective and functional domains has been associated with greater levels of satisfaction with treatment. 32 This evidence further highlights the importance of pain management which focuses beyond merely the reduction of pain severity to equipping chronic pain patients with the tools to help them participate in meaningful life roles and to reduce pain interfering with function. The one area that participants were less satisfied with in their pain management related to the amount of information received.…”
Section: Discussionmentioning
confidence: 95%
“…Previous data analysis demonstrated highly significant changes between admission and discharge ( p < 0.001) on the variables administered in the program such as pain intensity, depression, catastrophizing, anxiety, stages of change and pain acceptance ( 27 ).…”
Section: Methodsmentioning
confidence: 98%
“…Data were collected as described in Li and Hapidou ( 27 ). In short, participants were adults attending a four-week chronic pain management program from 2007 to 2017.…”
Section: Methodsmentioning
confidence: 99%
“…One study examined patient satisfaction in an interdisciplinary pain management program and found that integrating satisfaction measures with pain-related variables highlighted global change and improvement from the patients' perspective [97]. Another study focused on chronic intractable pain and found that treatments like physical therapy, interventional pain procedures, and spinal cord stimulation (SCS) resulted in acceptable patient outcomes [98]. A retrospective observational study evaluated the clinical results of endoscopic lesser trochanter resection in patients with ischiofemoral impingement and found that the procedure provided satisfactory outcomes with symptom relief and good functional results [99].…”
Section: Clinical and Functional Outcomesmentioning
confidence: 99%